Nucleic Acid Aptamer: A Novel Potential Diagnostic and Therapeutic Tool for Leukemia - Tan, Yuan (Onco Targets Ther, 2019)
Leukemia immunotherapy has been dominant via using synthetic antibodies to target cluster of differentiation (CD) molecules, nevertheless inevitable cytotoxicity and immunogenicity would limit its development. Recently, increasing reports have focused on nucleic acid aptamers, a class of high-affinity nucleic acid ligands. Aptamers purportedly serve as “chemical antibodies”, have negligible cytotoxicity and low immunogenicity, and would be widely applied for the therapy and diagnosis of various diseases, especially leukemia. In the preclinical applications, nucleic acid aptamers have displayed the augmented specificity and selectivity via recognizing targets on leukemia cells based on unique three-dimensional conformations. As small molecules with nucleic acid characteristics, aptamers need to be chemically modified to resist nuclease degradation, renal clearance and improve binding affinities. Moreover, aptamers can be linked with neoteric detection techniques to enhance sensitivity and selectivity of diagnosis and therapy. In this review, we summarized aptamers’ preparation, chemical modification and conjugation, and discussed the application of aptamers in diagnosis and treatment of leukemia through highly specifically recognizing target molecules. Significantly, the application prospect of aptamers in fusion genes would be introduced.